Students in the margins: Lesbian, gay, and bi+ students' perceptions of school climate and discrimination - Herry, Emily; Mulvey, Kelly Lynn (International Journal of LGBTQ+ Youth Studies, 2025)
This study examines how youth evaluate their school climate and experiences of discrimination within public schools in the Southeastern U.S. Participants included 9th (N = 499, M age = 14.67, SD = 0.66) and 10th (N = 360, M age = 15.63, SD = 0.61) grade students who reported on their school climate and experiences of teacher and peer discrimination. Findings showed that lesbian, gay, bi+ (LGB+) participants reported significantly higher levels of peer discrimination than their heterosexual peers. Boys and 9th graders reported significantly higher levels of teacher discrimination than did girls and 10th graders, respectively. Experiences of discrimination from peers and teachers were distinctly associated with participants' perceptions of their school climate. LGB+ adolescents reported less positive social relationships with teachers, perceptions of school discipline, opportunities for engagement, academic support, parental involvement, and school connectedness compared to their heterosexual peers. There were no significant differences in perceived exclusion based on sexual orientation. This study is an important step in continuing to understand school experiences of LGB+ adolescents within the Southeastern U.S.